PEMBERDAYAAN AKSARA MASYARAKAT PEDESAAN : EVALUASI PROGRAM KEAKSARAAN FUNGSIONAL PADA KELOMPOK “NGUDI KAWRUH” DI KELURAHAN PASAR KLIWON KOTA SURAKARTA - Riza Wulandari (CENDEKIA: Jurnal Studi Keislaman, 2017)
The problem of illiteracy is still a concern of the Government of the city of Surakarta majority experienced by communities with medium economies down. Surakarta has the Functional Literacy Programme for the illiterate. This is already underway so that necessary related Evaluation of the program. This study is a qualitative study aiming to find out the success of the functional Literacy Program in the group "Ngudi Kawruh" Neighborhood Pasar Kliwon in Surakarta. This research uses qualitative evaluation methods with the techniques of data collection through interviews and literature study. In the interview, obtained from the Program Manager, lecturer or Tutor and Citizens learn KF "NGUDI KAWRUH" as informants while on a study of the literature retrieved from primary data and secondary data from the parties concerned. The results showed 1) driving and fator barrier of Functional Literacy Programmes in the Pasar Kliwon, 2) the impact of the Improvement and the increased capacity of self. The impact of empowerment of the script has been done is very perceptible to the residents especially the participants in the program, this is because what is taught in the program of empowerment this script can be directly applied in daily life by the participants.